Kann man die Gebrauchstheorie der Bedeutung in der Semantik gebrauchen? - Robering, Klaus (HERMES - Journal of Language and Communication in Business, 2002)
The following article deals with some aspects of special theories of meaning – namely those which consider the meaning of a linguistic sign as a function of its use. Although this approach to meaning is commonly attributed to Wittgenstein, I do not aim at an interpretation or exegesis of this philosopher but rather at a systematic discussion of meaning-as-use-theories. In the first section, I discuss the very notion of a theory of meaning. The next section provides a list of criteria which a theory of meaning should fulfill in order to be a meaning-as-use-theory. The formal architecture of semantic theories is discussed in the third section and – dealing with the simpler case of a referential theory of meaning as an example – the fourth section explains how semantic theories are given a theoretical underpinning by being interpreted within a theory of meaning. The same is done for the case of meaning-as-use-theories in the final section.